Pathological and Histochemical Study on Mice Treated With Black Nightshade Solanum Nigrum L. and infected with Secondary Hydatid Disease - Nabeel E. Salih; Entisar Al kenany; Buthaina H. Al-Sabawi (College of Education for Pure Sciences, 2008)
ABSTRACT Histopathological and histochemical changes in the liver and spleen tissues of mice which was treated with alcoholic extract of Solanum nigrum and infected with secondary hydatid disease, were investigated with an ultimate goal of determining the role which might be played by the extract in modulating the immune system towards a better response to the hydatid disease. Results demonstrate the appearance of hepatomegaly and splenomegaly due to deposition of amyloidosis in liver and spleen, in addition to other changes such as fatty changes and hemosiderosis. Causes of these changes and the role played by the plant extract, as an immunomodulator, were discussed.